Mathematical Modeling For Upgrading Low Rank Coal To High Rank Coal - Chan, Chun Seng (Universiti Sains Malaysia, 2005)
A plant was designed and fabricated to carbonize the low rank coal to high rank coal that is environmental friendly pilot plant. The outcome of the semi-coke or high rank coal which are smokeless fuel, high carbon content, low moisture content and high calorific value. The reason to construct this plant is because the trend has shown that demand of the high rank coal will be increased. In order to save the cost of the production cost, the raw material should be decrease. Therefore we must use the existing low rank coal in the Malaysia rather than depend on the imported high rank coal. Due to the low rank coal can not be used as a fuel for domestic and industrial purpose; therefore we have to find the way to change the quality of the coal in the Malaysia. Mathematical model equation had been constructed to estimate the temperature distribution inside the carbonization chamber. The temperature distribution curve show concave curves at the center. This indicates that the carbonization (pyrolysis) of the coal was an endothermic reaction. Besides that, the simulation with assist with the software Ansys to the cylindrical packed coal bed also have been done. Undeniable the result get from the simulation also have a small deviation compare to the experiment. The result is confirmed that the reliabilities of the product qualities and environmental friendly pilot plant are suitable for commercialization.